WhatsApp and green activism: a netnography of mobilisation and engagement - Shahreza, Mirza; Basit, Abdul (Faculty of Communications Science, Dr. Soetomo University, 2025)
This study analysed the role of WhatsApp in mobilising environmental activist communities in the Ciputat Subdistrict, South Tangerang. WhatsApp has become the primary communication platform for disseminating information, coordinating activities, and fostering community engagement. This research employs a qualitative approach using netnography. Data were collected through in-depth interviews with 13 informants, comprising community leaders, members, and government representatives, as well as participant observation within the community’s WhatsApp group over a three-month period, from May to July 2024. The findings indicate that WhatsApp is effective for the rapid dissemination of critical information, such as environmental clean-up schedules, illegal dumping alerts, policy updates, and educational materials on waste management. WhatsApp also facilitates open discussions by providing a space for members to share opinions, personal experiences, and collaboratively develop action plans through group chats, multimedia sharing, and polls. However, several challenges were identified, including information overload, limited responsiveness from some members, constraints in facilitating in-depth discussions, and technical barriers such as unstable internet connectivity. Despite these obstacles, WhatsApp plays a significant role in strengthening social bonds among community members and fostering collaboration with local government authorities. This study concludes that WhatsApp can serve as an effective tool to support environmental movements at both local and national levels. Its effectiveness could be further enhanced by integrating other communication platforms to meet their existing limitations.